Association Analyses of Autonomic Dysfunction and Sympathetic Skin Response in Motor Subtypes of Parkinson's Disease - Wang, Jian-Yong; Wang, Meng-Yan; Liu, Rong-Pei; Li, Yan; Zhang, Wen-Yuan; Ovlyakulov, Begench; Zhang, Xiong; Zhu, Jian-Hong (Frontiers in Neurology, 2020)
Introduction: Autonomic dysfunction is a common and disabling non-motor symptom of Parkinson’s disease (PD). We aimed to understand autonomic dysfunction in PD motor subtypes, the pattern of sympathetic skin response (SSR) to motor asymmetry, and the association of SSR with autonomic and motor dysfunctions. Methods: A total of 101 PD patients of Han Chinese were included. Unified PD rating scale (UPDRS), scales for outcomes in PD-autonomic symptoms (SCOPA-AUT), orthostatic hypotension, and SSR were evaluated. Results: SCOPA-AUT and incidences of orthostatic hypotension and absent SSR were worse in the subtype of postural instability gait disorder (PIGD) than the subtypes of tremor dominant and intermediate. SSR latency and amplitude were asymmetrical corresponding to the accentuation of motor severity. Patients with absent SSR had worse UPDRS and SCOPA-AUT scores. SSR parameters of the severe side in patients with SSR showed no independent association with the scores. Conclusion: Our results support that autonomic dysfunction is more severe in the PIGD than other subtypes and demonstrate an asymmetry of SSR in PD patients. Absent SSR may indicate worse autonomic and motor symptoms, but SSR parameters are not sufficient to evaluate the severity of the dysfunctions.